Cross-Media Alliances to Stop Disinformation: A Real Solution? - Palomo, Bella (2021)
Social networks have surpassed their intermediary role and become gatekeepers of online content and traffic. This transformation has favored the spread of information disorders. The situation is especially alarming in Spain, where 57% of Spaniards have at some moment believed false news. Since 2016, First Draft has promoted several collaborative verification projects that brought together newsrooms to fact-check false, misleading and confusing claims circulating online during presidential elections in several countries. The main objective of this article is to study the collaboration forged between newsrooms in Spain in order to debunk disinformation contents in 2019 under the name of Comprobado (Verified) and the impact of this initiative. Applying a methodological approach based on non-participant observation, interviews, content analysis of reports, scientific articles, books and media archives, we examine the internal uses of this platform, how journalists verified public discourse, the strategies and internal agreements implemented, and the degree of participation of the 16 media involved. Results show that only half of the initiatives begun were transformed into published reports, and the media impact achieved was limited. Finally, we note that the principal reasons for the frustration of the project were its improvised implementation, due to the date of the election being brought forward, and the scant culture of collaboration in the sector. In Spain at least, cross-media alliances are still an exception.